Numerical investigation on film cooling characteristics of slot-sectional diffusion holes combined with an internal cross-flow channel. (25th November 2020) - Xu, Guang-Yao; An, Bai-Tao; Yu, Zhi-Qiang; Li, Chen
Highlights: The film cooling effectiveness of slot-sectional diffusion holes is far superior to the fan-shaped. The slot-sectional diffusion holes exhibit an asymmetric bi-peak effectiveness pattern. The rectangular diffusion hole with a large cross-sectional aspect ratio yields the highest film cooling effectiveness. The fusiform diffusion hole with an outer convex downstream wall is less affected by the cross-flow and rib turbulators. Abstract: Film cooling characteristics of several slot-sectional diffusion hole geometries were investigated in a perpendicular cross-flow channel using numerical methods. A traditional circle-sectional fan-shaped hole was compared as a baseline. Four slot-sectional hole geometries included two fusiform diffusion holes (upstream or downstream wall outer convex) and two rectangular diffusion holes (cross-sectional aspect ratio AS = 3.5 or 5.0). The cross-flow channel had an 8D × 8D square cross-section and divided into smooth, 45° rib and 135° rib channels. Compared with plenum-fed, the film cooling effectiveness profiles of the slot-sectional diffusion holes were all transformed to asymmetric bi-peak patterns under the influences of cross-flow. Compared with the fan-shaped hole, a considerable advantage in film cooling effectiveness was found, especially at moderate and high blowing ratios. The largest increase in spatially averaged effectiveness was 160%, 112% and 50% respectively in the smooth, 45° rib and 135° rib channel. The rectangular hole with a large cross-sectional aspect ratio always yielded the highest cooling effectiveness in the different cross-flow channels. ln the ribbed channels, the performance of the post rib hole was significantly higher than that of the pre rib hole. The discharge coefficients of the slot-sectional diffusion holes were slightly higher than the fan-shaped hole in the same cross-flow channel.